2021
DOI: 10.3390/ijerph18147558
|View full text |Cite
|
Sign up to set email alerts
|

Cariogenic Risk and COVID-19 Lockdown in a Paediatric Population

Abstract: The Severe Acute Respiratory Syndrome Coronavirus 2 disease COVID-19 pandemic caused several lifestyle changes, especially among younger people. The study aimed to describe the impact of eating habits, lifestyle, and home oral hygiene during the COVID-19 pandemic, on the cariogenic risk in the Italian paediatric population, by using an online survey. The survey was conducted through a virtual questionnaire divided into four parts: child personal and anthropometric data; oral health; child dietary habits (KIDME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 41 publications
6
38
2
1
Order By: Relevance
“…A study by Docimo R et al on cariogenic risk and COVID-19 lockdown in a pediatric population showed that only 18.6% of the participants had high adherence to a Mediterranean diet, recording an overall increase in sweets consumption and the number of meals. Moreover, Docimo R. et al showed that also the lifestyle habits before and during lockdown changed significantly, with an overall reduction of the sport activities during and after compared to before [ 22 ]. A national Italian survey evaluated eating habits and lifestyle changes in an adult population during COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Docimo R et al on cariogenic risk and COVID-19 lockdown in a pediatric population showed that only 18.6% of the participants had high adherence to a Mediterranean diet, recording an overall increase in sweets consumption and the number of meals. Moreover, Docimo R. et al showed that also the lifestyle habits before and during lockdown changed significantly, with an overall reduction of the sport activities during and after compared to before [ 22 ]. A national Italian survey evaluated eating habits and lifestyle changes in an adult population during COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar destes artigos estarem de acordo com os critérios de inclusão sobre alimentação e doença bucal, eles possivelmente foram realizados antes da pandemia e publicados nos anos de 2020 e 2021. Apenas um artigo, realizado por meio de questionário online, foi especifico sobre o risco de alimentação cariogênica durante o isolamento social (Docimo et al, 2021). Neste trabalho os autores fizeram, por meio de teleconsulta, um questionário aos pais e responsáveis sobre a mudança de alimentação durante a pandemia do COVID-19.…”
Section: Resultsunclassified
“…Hence, dental practitioners practiced these treatments to save tooth decay during the lockdown in this context. Meanwhile, a study has reported the risk of dental infections and decay during the pandemic and suggested dental care and hygienic habits to the children [ 31 ]. Therefore, this study represents the requirement of proper pediatric dental care during the pandemic, similar to the study of Wuhan children [ 32 ], where dental complications among the children were low due to oral health education and knowledge with promoting an attitude of dental care.…”
Section: Discussionmentioning
confidence: 99%